HUBUNGAN ANTARA IKLIM KERJA DENGAN PRODUKTIVITAS KARYAWAN MENYETRIKA UNIT GARMEN PT APAC INTI CORPORA SEMARANG - Megalestari Ratna Cendikia; Siswi Jayanti; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
One of the factors that led to decrease productivity was the work climate. Temperatures that are too hot can decrease muscle strength in the work so that the negative impact could occurs on work productivity. In PT Apac Inti Corpora Semarang, the most potential hazard were iron worker at finishing and sewing section. The purpose of this study was to determine the relationship between the working climate, in particular heat, with iron worker productivity in the garment unit of PT Apac Inti Corpora Semarang. The method of this research was explanatory research used cross sectional approach. The population in the study was 40 and the sample taken using total sampling technique. The variable in this study was the work climate and work productivity. Instruments variable were labor productivity used the target number of production workers, the working climate assessment used the Questemp 34 device, and characteristic instrument used questioner. Data analyze with Chi-square test with significance level of 0.05. The results showed that there are relationship between work climate (p-value=0.001), age (p-value=0.068), work period (p-value=0.066), and nutritional status (p-value=0.042) with work productivity.